Evaluación física, química y bacteriológica de las aguas del río Amazonas en la zona de Indiana - distrito de Indiana – provincia de Maynas – región Loreto - Guedes Rios, Juan Carlos (2023)
In the present research study, the physical, chemical and bacteriological parameters of the waters of the Amazon River - Indiana district - Maynas province - Loreto region were evaluated. For this, two samplings were carried out at different times (rising and emptying). The water quality study was set at four sampling points (P1, P2, P3 and P4) located along 450 meters of the shoreline of the Indiana district. The samples collected from monitoring were taken to the Industrial Chemical Analysis laboratory of the Faculty of Chemical Engineering UNAP and to the Microbiology laboratory of the Faculty of Food Industries for their respective analyses. Relatively significant results were obtained, such as phosphate (1.1 mg/L), magnesium hardness (30.5 mg/L), dissolved oxygen (6.1 mg/L) and oils and fats (9.3 mg/L) in times of increasing exceeded the LMP according to the RCTs; In periods of emptying, the pH (9.3), phosphate (1.4 mg/L), and oils and greases (14.2 mg/L) exceeded the LMP according to the ECAS. It was concluded that the parameters of pH, magnesium hardness, phosphate, dissolved oxygen, oils and greases exceeded the LMP, according to the ECAS and the other physical, chemical and microbiological parameters analyzed are within the LMP in accordance with the D.S. N° 004-2017-MINAM